Respostas
respondido por:
0
a18 = a1 + 17r
a1 = 2
a2 = 5
a3 = 8
r = a2 - a1
r = 5 - 2
r = 3
an = a1 + (n - 1).r
a18 = a1 + (18 - 1).r
a18 = a1 + 17r
a18 = 2 + 17.3
a18 = 2 + 51
a18 = 53
sn = (a1 + an).n
------------------
2
S18 = (a1 + a18).18
---------------------
2
S18 = (2 + 53).9
s18 = 55.9
s18 = 495
R.: S18 = 495
a1 = 2
a2 = 5
a3 = 8
r = a2 - a1
r = 5 - 2
r = 3
an = a1 + (n - 1).r
a18 = a1 + (18 - 1).r
a18 = a1 + 17r
a18 = 2 + 17.3
a18 = 2 + 51
a18 = 53
sn = (a1 + an).n
------------------
2
S18 = (a1 + a18).18
---------------------
2
S18 = (2 + 53).9
s18 = 55.9
s18 = 495
R.: S18 = 495
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás